American Studies in Russia - I. I. Ivanov (Контуры глобальных трансформаций: политика, экономика, право, 2022)
The article discusses the development of the American studies in the Soviet Union, in Russia, with focus on the key fields of investigations, the main centers for the United States studies; and periodicals where the results of these studies are being published. Different areas of the United States development have been the point of interest in Russia as long as they exist. The main contemporary centers for the American studies on a permanent basis were founded at the second half of the 20-th century. The American studies in the main centers of academic research, such as the Institute for the US and Canada studies, IMEMO, the Institute for General History, the Gorky Institute of World Literature, other academic institutes are being developed along with those in the leading universities, such as Moscow university, Saint Petersburg university; mgimo and many other universities (representing a wide number of regions in Russia) where American studies have become one of the academic disciplines. In focus - the periodicals where the results of the studies on different aspects of the United States policy, economic development, history, the views on American literature and culture are being published.